2018
DOI: 10.3390/ijms19051270
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Roles of Connexin Channels and Tunneling Nanotubes in Cancer Pathogenesis

Abstract: Neoplastic growth and cellular differentiation are critical hallmarks of tumor development. It is well established that cell-to-cell communication between tumor cells and “normal” surrounding cells regulates tumor differentiation and proliferation, aggressiveness, and resistance to treatment. Nevertheless, the mechanisms that result in tumor growth and spread as well as the adaptation of healthy surrounding cells to the tumor environment are poorly understood. A major component of these communication systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 211 publications
(280 reference statements)
0
33
0
Order By: Relevance
“…Interestingly, not only a hostile environment (inflammation, hypoxia, and inadequate pH) enhances TNT formation [4,[8][9][10][11], but also TNTs could contribute to the escape of the cells from the cell death induced by apoptosis [10,[12][13][14]. On the other hand, TNTs convey resistance to chemotherapy by exporting the mitochondria [15,16]. This transfer of mitochondria allows tumor cells to develop one of the hallmarks of tumors, i.e., a metabolic plasticity, in order to acquire migration, proliferation, and resistance properties, particularly to cisplatin and paclitaxel [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, not only a hostile environment (inflammation, hypoxia, and inadequate pH) enhances TNT formation [4,[8][9][10][11], but also TNTs could contribute to the escape of the cells from the cell death induced by apoptosis [10,[12][13][14]. On the other hand, TNTs convey resistance to chemotherapy by exporting the mitochondria [15,16]. This transfer of mitochondria allows tumor cells to develop one of the hallmarks of tumors, i.e., a metabolic plasticity, in order to acquire migration, proliferation, and resistance properties, particularly to cisplatin and paclitaxel [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory demonstrated that myeloid and glial cells within the CNS are viral reservoirs. These few viral reservoirs, despite the low to undetectable viral replication, are able to amplify toxicity and inflammation to neighboring uninfected cells by a gap junction, hemichannel, and tunneling nanotube mediated mechanism (Eugenin et al, 2009a , b ; Berman et al, 2016 ; Malik and Eugenin, 2016 , 2019 ; Ariazi et al, 2017 ; Okafo et al, 2017 ; Valdebenito et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…TNTs have also been found in primary human tumors [ 39 , 40 , 41 ]. It is becoming clear that TNTs facilitate a pathway of intercellular conduits in tumors [ 42 ] and may promote numerous malignant features such as invasion, growth, chemo- and radiotherapy resistance, and surgery-induced tumor growth [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Connexins localize to TNTs and regulate intercellular communication [ 44 , 46 , 47 ]. Wang et al [ 46 ] identified TNT-mediated voltage-sensitive electrical coupling that was inhibited by the gap junction inhibitor meclofenamate.…”
Section: Introductionmentioning
confidence: 99%